Measurement of Interrupter Respiratory Resistance and Spirometry in Preschool Children: Influence of Respiratory Symptoms. (September 2013) - Tancredi, G.; de Castro, G.; Rugiano, A.; Zicari, A.M.; Indinnimeo, L.; Nicolai, A.; Duse, M.
Pulmonary function tests play an important role in the diagnosis and management of respiratory diseases in children. The purpose of the study was to evaluate lung function using the interrupter resistance technique (Rint) and spirometry (flow-volume and volume-time) in preschool children and to correlate the findings with respiratory symptoms. We studied 103 children (65 males, 38 females; mean age 5.2±0.7 years; range 3.6–5.8). For each child we collected family history concerning: respiratory diseases, skin prick tests, smoking during maternal pregnancy, history of gestational and neonatal period. All children performed lung function tests (Rint and spirometry) and skin prick test for inhalant and food allergens. Twenty-eight subjects (27.2%) had respiratory symptoms (RS). Expiratory Rint were performed in all subjects and spirometry was carried out on 76 children (73.8%). Spirometric indices were not statistically different between subjects without respiratory symptoms (controls) and RS children except for FEF25–75 expressed as a percentage of the predicted value (RS: 81.5±13.7% vs controls: 94.5±15.8%; p <0.001). Rint mean values were significantly higher in RS children than in controls (RS: 135.6 ±24.8% vs controls: 102.4 ±21.7%; p< 0.0001). We found a statistically negative correlation between Rint and the following Spirometric indices: FEV0.5 (R= −0.696; p < 0.0001), FEV, (R= − 0.728; p < 0.0001) and FEF25–75 (R= −0.681; p < 0.0001). In preschool children with respiratory disease we found significantly higher mean values of Rint and lower FEF25-75 than in the control group and a significant negative relationship between Rint and Spirometric indices.